THE RESEARCH OF THE NOTION «HARMONY» IN THE CONTEXT OF PERSONAL VITAL VALUES - Hurlieva Tetіana (PSYCHOLOGICAL JOURNAL, 2018)
The article considers the concept of harmony in the context of vital personal values, their structure, hierarchy, dynamics, the conditions of moving onto a higher level. The understanding of harmony and harmonization of vital personal values and personal vital functions are presented in the theories of such important scholars as H.O. Bal, O.M. Leontiev, S.D. Maksymenko, A. Maslow, V.A. Petrovskii, S.L. Rubinstein, V.O. Tatenko, V. Frankl, V.E. Chudnovskii and many others. It is mentioned that in the studies of domestic and foreign scientists the notion of harmony is mostly revarded in the context of personal development, an individual’s relationships with other people and with the world. However, this study does not cover the semantic field of personality as a balanced and dynamic whole. By the harmony of vital values the author of the article implies such a correlation of the parts of semantic sphere that characterizes innerly consistent (taking some possible semantic disharmony into account) existence of vital personal values on a certain stage of their formation as a corporal, social and spiritual entity. The focus is on sublime, essential and spiritual values which enable the harmony of the personal semantic sphere, balance and streamline human needs and ensure a bottom-up vector of their development. The results of the scientific research as well as personal presumptions allow to ascertain the presence of harmony in relative disharmony of formed vital values, which in their connection and interrelation enhance successful personal development. An explanation is given of constructive and destructive semantic disharmonies. The article highlights the importance of harmonization of vital values in adolescence and youth. From the position of humanistic psychology, the perspectives of psychological assistance in harmonizing vital values are outlined. It is considered that it is a dialogue and dialogue-like communication which are the conditions to a person seeking and revealing their meaning of life and harmonizing their personal sphere of values. This communication occurs mainly between a psychologist and client, seeking psychological assistance in case of the loss of meaning of life or disorientation in this sphere.